Ameliorative effects of propolis and wheat germ oil on acute toxoplasmosis in experimentally infected mice are associated with reduction in parasite burden and restoration of histopathological changes in the brain, uterus, and kidney - Elmahallawy, Ehab Kotb; Ali, Fatma Abo Zakaib; Raya-Álvarez, Enrique; Fehaid, Alaa; Abd El-Razik, Khaled A.; El Fadaly, Hassan Ali Mohamed; El-Khadragy, Manal F.; Sayed, Amal S. M.; Soror, Ashraf H.; Alhegaili, Alaa S.; Saleh, Amira A.; Alkhaldi, Abdulsalam A. M.; et al. (Frontiers in Veterinary Science, 2024)
Toxoplasmosis continues to be a prevalent parasitic zoonosis with a global distribution. This disease is caused by an intracellular parasite known as Toxoplasma gondii, and the development of effective novel drug targets to combat it is imperative. There is limited information available on the potential advantages of wheat germ oil (WGO) and propolis, both individually and in combination, against the acute phase of toxoplasmosis. In this study, acute toxoplasmosis was induced in Swiss albino mice, followed by the treatment of infected animals with WGO and propolis, either separately or in combination. After ten days of experimental infection and treatment, mice from all groups were sacrificed, and their brains, uteri, and kidneys were excised for histopathological assessment. Additionally, the average parasite load in the brain was determined through parasitological assessment, and quantification of the parasite was performed using Real-Time Polymerase Chain Reaction targeting gene amplification. Remarkably, the study found that treating infected animals with wheat germ oil and propolis significantly reduced the parasite load compared to the control group that was infected but not treated. Moreover, the group treated with a combination of wheat germ oil and propolis exhibited a markedly greater reduction in parasitic load compared to the other groups. Similarly, the combination treatment effectively restored the histopathological changes observed in the brain, uterus, and kidney, and the scoring of these reported lesions confirmed these findings. In summary, the present results reveal intriguing insights into the potential therapeutic benefits of wheat germ oil and propolis in the treatment of acute toxoplasmosis.